TECHNOLOGY USE IN IPS IN SMP LEARNING - Mustopa; Rismiwati; Moh. Imron Rosidi; Abdul Wahab Syakhrani; Iyad Abdallah Al- Shreifeen (International Journal of Teaching and Learning, 2024)
The literature review carried out was aimed at empirically measuring the use of technology in social studies learning. This involves monitoring, measuring, and analyzing the effectiveness of technology in improving student understanding, information retention, and learning outcomes. Evaluate educational policies that support or hinder the integration of technology in the teaching and learning process. In this modern era, technology has become an integral component in education, with significant implications on how learning and teaching is conducted. With the existence of educational technology and learning technology in this social studies education study, students will be more enthusiastic, active and continue to try in terms of learning. Because as the era develops, education must also follow it as long as it is positive and has a good impact on educators and their students. Therefore it is very helpful in a learning environment. Usually in learning using a projector, laptop, salon, microphone etc. It is very helpful for educators and students to grasp or be sensitive to current learning concepts.